Pengaruh Fatwa Majelis Ulama Indonesia terkait Legalitas Bitcoin sebagai Aset Digital di Indonesia - Ihsan Kurniawan; Nuzul Rahmayani; Jasman Nazar (UNES Law Review, 2023)
This study aims to explain how the legality of bitcoin as a digital asset in Indonesia is viewed from Indonesian positive law and the influence of the MUI fatwa regarding the legality of bitcoin as a digital asset. The problem here is that even though MUI has issued a Fatwa regarding the haram of Bitcoin both as a means of payment and as a digital asset, cryptocurrency transactions are mostly used as speculation which results in elements of gharar and maysir. But until now the use of crypto money has not decreased and even arguably more enthusiasts. From this research, it was found that Bank Indonesia responded that Bitcoin does not have legality as a legal transaction tool in Indonesia and is considered legal if Bitcoin is used as a crypto asset in the commodity futures exchange. Bappebti noted that the total number of crypto investors until the end of August 2022 has amounted to 16.1 million investors, which indicates that the number of crypto investors has increased by around 43.75% in the January-August 2022 period, experiencing a very high increase so that the influence caused by the MUI fatwa regarding the haram of bitcoin as a digital asset is not so significant because the nature of the MUI fatwa is only personal for someone who is Muslim. This research is expected to be a material and reading source for students to increase their knowledge and become a foundation for other researchers in the future.